Owner and Veterinarian Perceptions About Use of a Canine Quality of Life Survey in Primary Care Settings - Mwacalimba, Kennedy K.; Contadini, Francesca M.; Spofford, Nathaniel; Lopez, Karen; Hunt, Aimee; Wright, Andrea; Lund, Elizabeth M.; Minicucci, Larissa (Frontiers in Veterinary Science, 2020)
This paper describes dog owner and veterinarian perceptions around the use of a validated canine quality of life (QOL) survey to facilitate wellness conversations in two clinical settings: a veterinary teaching hospital (pilot, Phase 1) and five corporate general practice hospitals (Phase 2). Phase 1 results showed that dog owners felt the survey was valuable for understanding their dog's QOL, with 81% of owners expressing interest in learning more about canine QOL. Phase 2 reinforced owner perceptions about the survey conveyed during the pilot phase, and veterinarians reported that the survey facilitated client communication related to preventive care without increasing consultation time. These results demonstrate that beyond using QOL assessments to track patient health, the use of a QOL survey during veterinary visits could improve owner-veterinarian discussions around QOL, wellness, services and preventive care. To fully realize these benefits in clinical settings, veterinary staff preparation may be needed to communicate the purpose of QOL assessments to clients and thus facilitate deeper conversations about client needs and concerns. Key tools for achieving these could therefore include (1) sufficient veterinary team training to understand the QOL assessment and its purpose (2) training in how to communicate QOL to clients, and (3) reflexive use of QOL assessment results to engage clients in preventive care discussions. The veterinarian and client can then discuss the pros and cons of the various aspects of QOL and preventive care to arrive at a cooperative decision.